2021
DOI: 10.26452/fjphs.v1i1.143
|View full text |Cite
|
Sign up to set email alerts
|

test

Abstract: abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Literature indicates that multiple resistive states in RRAM devices can be realized through methods like modulating current compliance during the set process, [28,39,40] adjusting the reset stop voltage in the reset process, [28,32,41] using light illumination, [39,42] and tweaking pulse width. [5,27] In many studies, the multilevel resistance states in lead-free perovskite memory devices have been manipulated by adjusting the current compliance during the set process. [31,[43][44][45][46][47][48] In our study, multiple HRS states (R2-R6) were achieved by incrementing the reset stop voltage from 2 to 6 V at intervals of 1 V (Figure 2g).…”
Section: Rram Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature indicates that multiple resistive states in RRAM devices can be realized through methods like modulating current compliance during the set process, [28,39,40] adjusting the reset stop voltage in the reset process, [28,32,41] using light illumination, [39,42] and tweaking pulse width. [5,27] In many studies, the multilevel resistance states in lead-free perovskite memory devices have been manipulated by adjusting the current compliance during the set process. [31,[43][44][45][46][47][48] In our study, multiple HRS states (R2-R6) were achieved by incrementing the reset stop voltage from 2 to 6 V at intervals of 1 V (Figure 2g).…”
Section: Rram Applicationmentioning
confidence: 99%
“…[ 4 ] However, these devices also face challenges related to variability, data retention, write disturbances, and multilevel cell stability, to list a few. [ 5 ] In this sense, the pursuit of RRAM materials that promise higher performance, better energy efficiency, and novel functionalities remains incessant. [ 6 ] Accordingly, an emerging class of materials such as perovskites has attracted intense interest given their potential, such as higher On/Off ratios, reduced switching voltages, unique optical multiple functionalities, and compatibility with novel flexible form factors, among others.…”
Section: Introductionmentioning
confidence: 99%
“…[ 15–18 ] Despite the wide range of advantages of memristive devices in neuromorphic computing, there are still several challenges at the device level such as poor stability, high variability, poor retention, and endurance. [ 19 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 18,27 ] Because of the stochastic and abrupt nature of these processes, large device‐to‐device and cycle‐to‐cycle variations have frequently been observed. [ 2,19 ] This further results in wide variations in the set/reset voltage, on/off ratio, endurance, retention and switching speed, and therefore, hindering their practical realization. [ 28–31 ] More recently, significant attention has been given to interface‐type (IT) RS devices, which exhibit uniform and nondestructive resistance change induced by an interface Schottky barrier modulation.…”
Section: Introductionmentioning
confidence: 99%
“…[2,3] In order to expand multi-bit storage capacity without sacrificing additional 2D area, it has been shown that resistive switching random access memory (RRAM) is capable of demonstrating multilevel memory states by modulating its internal state parameters. [4,5] The RRAM is one of the classes of memory concepts that is based on the electrical stimulation-induced change in resistance of a metal-insulator-metal (MIM) memory structure. [6,7] The crude classification of RRAM devices is based on the working principle, in which one device operates entirely on the migration and redistribution of cations, such as Cu or Ag, Mg, and Al, etc.…”
Section: Introductionmentioning
confidence: 99%